The Implementation of Musyarakah Mutanaqisah in Islamic Banks: Strengthening the Role of Islamic Financing in Indonesia - Kartika, Irina; Habsyah, Ade; Azwari, Peny Cahaya (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the application of Musyarakah Mutanaqisah (MMQ) in Indonesian Islamic banking as a more equitable partnership-based financing model that is in line with the principle of risk sharing. Although Indonesia has great potential in the development of Islamic finance, the proportion of MMQ financing is still low. This study uses a qualitative descriptive approach with a literature review of current research and regulations to explore the supporting factors, obstacles, and the role of Islamic literacy in the success of MMQ. The results show that regulatory support and institutional readiness are the main drivers in the implementation of MMQ. On the other hand, contract complexity, inconsistent standards, and low customer literacy are the main obstacles. These findings indicate that to strengthen the role of MMQ, good regulatory synergy, institutional capacity building, process digitalization, and broader Islamic financial education are needed. With these steps, it is hoped that MMQ can become a more inclusive and sustainable financing alternative, providing benefits not only for financial institutions but also for society as a whole. Through the strengthening of Islamic financial literacy, it is hoped that customers will be able to understand and utilize MMQ products to the fullest, thereby driving the growth of the Islamic finance sector in Indonesia.